Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Pada Café & Restoran Kokok Petok Di Cimalaya Wetan - Robby Syuhada; Puji Isyanto; Dini Yani (Faculty of Economics and Business, Universitas Malikussaleh, 2023)
This study aims to examine the marketing strategy to increase sales at the Kokok Petok Cafe Restaurant and find out the strengths, weaknesses, opportunities, and threats at the Kokok Peto Cafe Restaurant as well as formulate an alternative competitive marketing strategy that is superior using the SWOT analysis method. This study uses descriptive research methods. The data collection technique of this research used observation, interview, documentation, and literature study methods. The data analysis technique used the SWOT analysis method with the SWOT matrix model. The results showed that marketing strategies to increase sales in terms of product, price, distribution, and promotion affected the performance of Kokok Petok Cafe Restaurant. SO, ST, WO, and WT strategies also affect the performance of Kokok Petok Cafe Restaurant. Based on calculations using SWOT analysis, it can be concluded that the position of Kokok Petok Cafe Restaurant is in quadrant II which shows Kokok Petok which is in a steady situation but faces some serious challenges. So the company will have difficulty if it only relies on the previous strategy. Therefore, the company is advised to start increasing the variety of its tactical strategy. With this research, it is expected to make a marketing strategy that is carried out to increase sales at the Kokok Petok Cafe Restaurant.